2020
DOI: 10.3390/brainsci10070410
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Physical Therapy for Individuals with Rett Syndrome: A Systematic Review

Abstract: Rett syndrome is a rare genetic disorder that affects brain development and causes severe mental and physical disability. This systematic review analyzes the most recent evidence concerning the role of physical therapy in the management of individuals with Rett syndrome. The review was carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. A total of 17319 studies were found in the main scientific databases. Applying the inclusion/exclusion criteria, 22 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…17 Recent systematic reviews of physical therapy interventions for individuals with RTT have reported mostly positive effects on gross motor skills, motor endurance and fitness within therapy settings. [18][19][20] Opportunities for training have been observed as enjoyable for the child when accompanied with a microswitch that delivered a light and sound sensory response to walking. 21 We note that the majority of studies were case studies, case series and single-case design studies, and only one study used randomisation in a stepped wedge design.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recent systematic reviews of physical therapy interventions for individuals with RTT have reported mostly positive effects on gross motor skills, motor endurance and fitness within therapy settings. [18][19][20] Opportunities for training have been observed as enjoyable for the child when accompanied with a microswitch that delivered a light and sound sensory response to walking. 21 We note that the majority of studies were case studies, case series and single-case design studies, and only one study used randomisation in a stepped wedge design.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, physical therapy is another essential intervention for the management of bone health in this disorder [30,132,133]. In this regard, a systematic review of the literature identified nine different approaches to physical therapy used in RTT that demonstrated to improve the quality of life in these patients, mostly helping to maintain autonomy [134].…”
Section: Therapeutic Approaches For Bone-related Issues In Rttmentioning
confidence: 99%
“…To date, there is no cure for disorders such as AS because there are still no definitive ways of repairing chromosomal defects or of restoring function to mutated genes. At present, optimal care management and rehabilitation are the only options for improving the health-related quality of life in children affected by neuromuscular disorders [12][13][14][15][16][17][18][19][20][21]. In such conditions, the goal of rehabilitation is to achieve and maintain optimum functioning in interaction with environments, following the International Classification of Functioning (ICF) approach to disability, which understands functioning and disability as a dynamic interaction between the health condition and contextual factors, both personal and environmental [22][23][24].…”
Section: Introductionmentioning
confidence: 99%